2018
DOI: 10.4103/1735-5362.235159
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydroalcoholic extracts of Trifolium pratense L. on pancreatic β cell line (RIN-5F) against cytotoxicty of streptozotocin

Abstract: Natural plants have traditionally been used throughout the world for their anti-diabetic effects. The aim of the present study was to investigate the protective effect of hydroalcoholic extract of Trifolium pratens L. (T. pratense) on streptozotocin (STZ) cytotoxicity and insulin concentration from RIN-5F pancreatic β cell line. In this study, possible cytoprotective action of T. pratense extract (using pre-treatment, simultaneous, and post-treatment schedules) against STZ (30 mM) was evaluated using MTT assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For this reason, many studies have been conducted to evaluate the potential lipid-lowering activity of synthetic and natural compounds ( 6 ). It has been suggested that herbal remedies are among the best existing alternative therapies and have been used since ancient times ( 7 ) and they have contributed to the development of important drugs used currently in modern medicine ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many studies have been conducted to evaluate the potential lipid-lowering activity of synthetic and natural compounds ( 6 ). It has been suggested that herbal remedies are among the best existing alternative therapies and have been used since ancient times ( 7 ) and they have contributed to the development of important drugs used currently in modern medicine ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The work was done in the dark, and after three times of rinsing cells with PBS, they were observed through a fluorescence microscope. 29 The apoptotic index of the cells was calculated using the following formula Apoptotic index = number of apoptotic cells/total number of cells 100×…”
Section: Tunel Stainingmentioning
confidence: 99%
“…This disease is the most common chronic disorder in the whole world. It is estimated that by 2030, the number of people suffering from the disease will reach more than 370 million ( 3 ). Increased generation of reactive oxygen species and the occurrence of oxidative stress led to the destruction of insulin-secreting beta cells of the islets of Langerhans.…”
Section: Introductionmentioning
confidence: 99%